Physical work environment, job design, and job satisfaction: Transformational leadership as a boundary condition - Raden Muhammad Arya Pratama; Neuneung Ratna Hayati (Jurnal Fokus Manajemen Bisnis, 2026)
Architecture and engineering consultancies depend on specialized expertise and durable client relationships. When dissatisfied professionals leave, firms risk losing tacit design knowledge and client-specific insights that are difficult to replace. In project-based professional service work, these retention risks make job satisfaction a strategically important outcome. The present study investigates the relationships among the physical work environment, job design, transformational leadership, and job satisfaction. It tests whether transformational leadership amplifies the satisfaction-relevant effects of both work conditions and task design features. Data were collected from 174 matched professionals using a two-wave time-lagged census survey with a four-week interval. Hypothesis testing employed variance-based structural equation modeling in SmartPLS, with statistical inference based on 5.000 bootstrap iterations. The results show that physical work environment, job design, and transformational leadership were positively associated with job satisfaction, with job design showing the strongest direct effect. Transformational leadership also strengthened the positive effects of physical work environment and job design on job satisfaction, although these interaction effects were modest in magnitude. The full model accounted for 55.7 percent of the variance in the outcome construct, indicating substantial explanatory coverage. These findings indicate that job satisfaction in project-based consultancy work depends not only on work conditions and task design but also on leadership quality, suggesting that retention can be supported through coordinated improvements in job design, physical work conditions, and leadership capability.